TINGKAT LITERASI ILMIAH BUKU PEMBELAJARAN BIOLOGI KELAS XI - Putri Novi Ani Sinaga; Mariani Natalina; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to describe the level feasibility of biology learning book according to the National Education Standards Agency (BSNP) and level scientific literacy of biology learning book for 11th grade based on four dimensions, namely science as the body of knowledge, science as a way of thinking, science as a way of investigation and science and its interaction with technology and society. This study uses a quantitative approach with the content analysis method. The sample in this study is the Biology Learning Book for 11th grade by Irnaningtyas and Yossa Istiadi revised in 2016 curriculum 2013 which was selected by purposive sampling technique. The research data were obtained from the results of book feasibility and the level of scientific literacy by using book feasibility instruments according to the BSNP and a sheet of scientific literacy level analysis based on 4 dimensions. Stages of analysis are divided into 2 stages, namely the stage of book feasibility analysis and analysis of the level scientific literacy of biology learning book. Data analysis using descriptive statistical methods. The results of data analysis show that the level of feasibility in the analyzed learning book has been declared feasible according to BSNP. At the level of scientific literacy, only the scientific dimension as a body of knowledge gets a good category. These results can then be used as material in the development of learning books based on the content of 4 dimensions of balanced scientific literacy. Key Words: Level of Literacy, Scientific Literacy, Learning Book, Curriculum 2013.